Use of renal contrast-enhanced ultrasound to explore renal cortical microcirculation abnormalities in pediatric acute kidney injury - Yi, Chunbei; Zhang, Fang; Shi, Jing; Zhang, Jian; Du, Jun (Frontiers in Pediatrics, 2025)
ObjectiveTo explore the correlation between the quantitative analysis curve of renal contrast-enhanced ultrasound and the anatomical location of renal cortical microcirculation associated with acute kidney injury.MethodsThis study included a 1-year-and-11-month-old female child with acute kidney injury caused by drug overdosed and a 14-year-old female child with acute kidney injury caused by drug intentional, who were treated at Shanghai Children's Medical Center affiliated with Shanghai Jiao Tong University School of Medicine. Both patients underwent renal contrast-enhanced ultrasound and quantitative analysis. In addition, their clinical medical history data were recorded.ResultsThe first child developed acute kidney injury owing to cyclosporine A overdosed. Contrast-enhanced ultrasound revealed poor cortical blood flow perfusion in both kidneys, with abnormally prolonged cortical perfusion times and possible obstruction of vascular inflow pathways. The second child experienced acute kidney injury owing to ibuprofen intentional. Contrast-enhanced ultrasound showed good cortical blood wash-in/perfusion but significantly delayed wash-out/excretion.ConclusionThe structure and function of the glomerulus significantly influence the perfusion rate and intensity of the rising branch of the curve. Furthermore, the descending branch of the curve is affected by the interplay of the capillaries surrounding the renal tubules. Exploration of these anatomical structures aids in understanding the renal microcirculation pathways and provides further insight into renal perfusion dynamics.